Career Counselling Services Centres in Public Universities in Azerbaijan - Malahova, Lamiya; Bayramova, Latafat; Ulukhanova, Ulkar (ADA University, 2022)
Career counselling services centres are essential for many public university students in the Republic of Azerbaijan. The purpose of this explorative qualitative study was to explore career counselling services centres at three public universities in Azerbaijan, the roles and responsibilities of career counsellors and administrators of the career counselling services centres, and the third- and fourth-year students’ perceptions of career counselling services. For planning and modifying the main study, the pilot study was conducted in one of the public universities in Azerbaijan. Qualitative semi-structured interviews were carried out with three administrators of the career counselling services centres, three career counsellors, and six students from three public universities in Azerbaijan. Additionally, the Capstone team wrote memos to avoid losing any detail of the collected data. Moreover, we conducted member checks to re-establish the results by seeking participant comments on the accuracy of verbatim claims. The collected data were analyzed based on the thematic map. The thematic analysis revealed several findings regarding the roles and responsibilities of administrators and career counsellors (organizing meetings, establishing contact with enterprises, and providing career advising), third- and fourth-year students’ perceptions of career counselling services (getting experience in professional and educational fields, being involved in internship programs), and obstacles that career counselling services centres encountered (lack of financial support, small number of staff members).
Keywords: Career counselling services.; Education, Higher -- Azerbaijan.; Education, Higher -- Azerbaijan -- Career counselling services.; Education